STRATEGI PEMASARAN DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA WISATA KULINER PERSPEKTIF PARIWISATA SYARIAH (STUDI KASUS LOS LAMBUANG BALAI KURAI TAJI KOTA PARIAMAN) - Riska Mahmuda; Khadijah Nurani (CV. Adiba Aisha Amira, 2024)
This writing is based on the background of consumers at the Los Lambuang Culinary tour at Kurai Taji Hall experiencing fluctuations in the number of consumers. The marketing strategy carried out by the sellers at the Los Lambuang Culinary Tourism Hall Kurai Taji is not optimal. There is no halal certification at the Los Lambuang Culinary Tourism Hall Kurai Taji. This is the aim of these findings, namely to identify marketing strategies applied to the Los Lambuang Culinary Tourism, Balai Kurai Taji, Pariaman City. The findings that have been researched use the type of research used in this research, namely descriptive qualitative research. From the results of this research, marketing strategies to increase consumer buying interest at Los Lambuang Balai Kurai Taji, Pariaman City from a sharia tourism perspective use the 7P marketing mix including: products by providing quality raw materials purchased in traditional markets with conditions still fresh, quality produce with delicious and distinctive taste, and a wide variety of food available. The price is set in accordance with purchasing power and the quality of the product being sold. The location of Los Lambuang is easy to access because it is close to the train station, visibility is easily visible to many people, and has safe parking. Promotion is carried out through social media and worth of mouth. People by recruiting employees through selection and training, serving consumers is carried out with a friendly and personal approach. The process involves cooking directly in a separate kitchen, using complete equipment and indirect service via telephone. Physical evidence, a clean room appearance and a beautiful view.